The doctrine of the directing mind and will of the company and the role of corporate "personality" - Laubscher, Peter (Department of Commercial Law, 2023)
The most famous if not the first recorded use of the phrase "directing mind and will of the company" was by Viscount Haldane in Lennard's Carrying Co Ltd v Asiatic Petroleum Co Ltd [1915] AC 705; [1914-15] All ER 280 (HL), 283C-D, hereinafter referred to as Lennard.